Mucosal immune responses induced by oral administration recombinant Bacillus subtilis expressing the COE antigen of PEDV in newborn piglets. Issue 3 (15th March 2019) - Wang, Jialu; Huang, Lulu; Mou, Chunxiao; Zhang, En; Wang, Yongheng; Cao, Yanan; Yang, Qian
Abstract : Porcine epidemic diarrhea (PED) is a highly contagious disease in newborn piglets and causes substantial economic losses in the world. PED virus (PEDV) spreads by fecal–oral contact and can be prevented by oral immunization. Therefore, it is necessary to develop an effective oral vaccine against PEDV infection. Currently, Bacillus subtilis as recombinant vaccine carrier has been used for antigen delivery and proved well in immune effect and safety. The present study evaluated the immunogenicity of recombinant Bacillus subtilis (B. subtilis -RC) in piglets via oral administration. After oral immunization in piglets, B. subtilis -RC significantly increased the local mucosal immune responses. Oral administration with B. subtilis -RC significantly improved the level of specific mucosal immunoglobulin A (IgA) antibodies against PEDV infection, through enlarging the area of Peyer's patches (PPs) and increasing the number of ileum IgA + secreting (SIgA) cells. In the meantime, B. subtilis -RC remarkably increased the number of intraepithelial lymphocytes (IELs). We also observed that oral administration of B. subtilis -RC significantly increased CD3 + T lymphocytes' numbers and up-regulated the ratio of CD4 + /CD8 + T cells. Furthermore, high titers of specific serum immunoglobulin G (IgG) revealed satisfactory systemic immune response against PEDV infection. In summary, our study demonstrated that oral administration of B. subtilis -RC could trigger a high level of local and systemic immune responses and would be a promising candidate vaccine against PEDV infection in piglets.